FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN (Students' Journal of Accounting and Banking, 2013)
The study was conducted to analyze the effect of Return On Equity (ROE), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Price Earnings Ratio (PER) and Earning Per Share (EPS) of the company's value proxied by Price to book Value (PBV). The study object is the banking company listed on the Indonesia Stock Exchange (BEI) in 2008-2011 using the total sample of 25 companies per year. The data analysis technique used is multiple linear regression equation least squares and test hypotheses using tstatistics for testing the partial regression coefficients and  Fstatistics to test the significance effect together with a significance level of 5%. During the observation period of the study showed that the data were normally distributed. Under normality test, multicollinearity, heteroscedasticity test and autocorrelation test is not found in the classical assumption variables deviate. This shows the available data has been qualified using multiple linear regression equation models. The results of this study indicate that the LDR and NIM variables showed no significant effect on firm value. Variable ROE, EPS and PER significant positive effect on firm value. Predictive ability of the five variables on firm value in this study of 34.8% while the remaining 65.2% influenced by other factors not included in the research model.Keywords: Return On Equity (ROE), Loan to Deposit Ratio (LDR), Net InterestMargin (NIM), Price Earnings Ratio (PER), Earning Per Share(EPS) and the value of the Company.